EXAMINING CRISIS COMMUNICATION AND ONLINE ACTIVISM IN INDONESIA: A CASE STUDY ON 2022 VOTRE PEAU - Veritasia, Mytha Eliva; Suteja, Rani Sukma Ayu (Jurnal Ilmu Komunikasi UHO : Jurnal Penelitian Kajian Ilmu Komunikasi dan Informasi, 2024)
This article discusses the crisis experienced by a local beauty brand, Votre Peau, in 2022, following an internal event featuring a "best dress challenge" that was heavily criticized by netizens for being perceived as disrespectful towards Islam and women. This crisis drew condemnation from netizens and sparked an online movement to boycott or cancel the brand due to consumer dissatisfaction. The research aims to examine the crisis communication strategies employed by Votre Peau in response to online activism. Qualitative data analysis is conducted through a case study utilizing concepts from digital activism and image repair theory by William L. Benoit. The analysis findings indicate that Votre Peau implemented image repair strategies by providing open clarifications and apologies on social media. Despite these efforts, disgruntled consumers feel that the approach was ineffective and continued the cancel culture movement against Votre Peau. An intriguing aspect is the slactivism paradox, which shows a decline in the trend of the boycott movement simultaneously with the decrease in its virality. This article contributes to underscores the importance of crisis communication strategies as rapid dialogue dissemination in digital media can profoundly impact the company's or brand’s reputation. Therefore, having a good crisis communication strategy is crucial for addressing various situations, especially in digital era like today.